Scaling-Up Sweetpotato through Agriculture and Nutrition (SUSTAIN) in Rwanda - International Potato Center (2017)
The project has set up 39 DVMs (46% male, 54% female). After four years, we have reached 102,038 beneficiaries in 8 districts with an adoption rate of 96% measured as those are still growing OFSP at least two years after receiving the vines. Average yields have increased from 3-5 t/ha to 12 -15 t/ ha. During the past year (1st July 2016 to 30th June 2017), agro-processors marketed processed products worth US $199,723 and DVMs sold vines worth US $41,114.